TAPHONOMIC ASPECTS OF THE MIOCENE ICHNOFOSSIL-LAGERSTÄTTE FROM CALCARENITE TURBIDITIC BEDS IN THE VERGHERETO MARLS (NORTHERN APENNINES, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
Five, 3-8 cm-thick calcarenitic turbiditic beds belonging to overbank deposits in the marginal sector of Marnoso-arenacea Basin, close to the intrabasinal high of Verghereto (Romagna, Northern Apennines, Upper Miocene), exhibit a well preserved ichnofossil-lagerstätte.The lagerstätte is composed by 43 ichnotaxa: 31 of them are preserved as casts at the sole of turbidites (background hypichnia) (group a), while 12 of them occur at the top (post-turbidite epichnia) and within (endichnia) (group b). The ichnodensity reaches its maximum at the top of the turbiditic beds. Background hypichnia (group a) is represented by graphoglyptids and non-graphoglyptid resting traces (background ichnofauna), with three-dimensional networks and shafts, meander systems, radiate, plug-shaped or stellatae structures forming clusters and unbranched systems of strings. Many taphonomic features suggest a fluting induced by bottom currents; graphoglyptids should have colonised the substrate after the action of these currents being not destroyed or fluted. All hypichnial structures are perfectly preserved by the turbidite casting and in this phase also endichnial burrows could develop. Post-turbidite epichnia (group b) concern vagile feeding burrows that developed horizontal patterns in a post-turbiditic regime, during the suspension phase of fine material; they were probably produced by organisms transported by suspension flows. Here, the very high ichnodensity suggests a competition among burrowers under stable currents with occurrence of vagile opportunistic organisms immediately followed by others that produced radiate spreite structures.   SHORT NOTE
Keywords: Ichnology; Lagerstätte; Taphonomy; Trace fossils; Turbidites; Miocene; Apennines